Effect of metallic nanostructure's shape and size on the performance of organic solar cells: A simulation study / Rupak Wasman Qadir - Wasman Qadir, Rupak (2015)
A systematic study on the absorption enhancement by embedding the periodic metallic nanostructures (NSs) inside the organic Copper Phthalocyanine (CuPc) thin films, is reported. The Surface Plasmon resonance (SPR) can be excited by adding metallic nanostructures and the light can be concentrated and folded into the CuPc layers. By utilizing the Finite Different Time Domain (FDTD), the role of the several different shapes of the metallic nanostructures has been studied. It has been found that the metallic NSs can result in a broadband optical absorption enhancement within the semiconductor thin film in organic solar cells. By increasing the optical path length, the probability of photon being absorbed within the thin film, is increased. The studies on the effects of the position, the dimension and spacing of the metallic particles in the organic thin film on the light absorption have also been performed. A significant enhancement in the absorption in the wavelength range of 350-550 nm has been observed. Furthermore, the investigation has been performed on the effect of the light source incident angle and polarization direction on the absorption in the organic thin films. The best incident angle is found at 75 degree. The role of the nanoparticles light scattering for enhanced light absorption in the organic solar cells, also has been investigated. It is found that the size and shape of nanoparticles give a significant effect on the light scattering and absorption spectra over the visible wavelength.